1997
DOI: 10.1111/j.1469-7998.1997.tb05762.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization and land tenure system of the endangered Iberian lynx (Lynx pardinus)

Abstract: The spatial organization of the endangered Iberian lynx, Lynx pardinus (Temminck, 1827), was studied in Dofiana National Park, south-western Spain, between 1983 and1992. Thirty-six individuals (19 males and 17 females), including 24 adults (13 males and 1 1 females) were radio-tracked, providing 13,950 locations during 17,l I 1 radio-tracking days. Iberian lynxes were essentially solitary (95.9% of simultaneous locations apart) and interactions were restricted to rearing activities by females. Adult associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(154 citation statements)
references
References 44 publications
6
146
2
Order By: Relevance
“…These studies also found both sexes to maintain home ranges with extensive inter-sexual, but little intra-sexual, overlap suggesting intra-sexual resource defence through territoriality. The same seems to be common in related species, ie Iberian lynx Lynx pardinus (Ferreras et al 1997), Canadian lynx Lynx canadensis (Poole 1995) and bobcat Lynx rufus (Lovallo and Anderson 1996).…”
Section: Discussionmentioning
confidence: 79%
“…These studies also found both sexes to maintain home ranges with extensive inter-sexual, but little intra-sexual, overlap suggesting intra-sexual resource defence through territoriality. The same seems to be common in related species, ie Iberian lynx Lynx pardinus (Ferreras et al 1997), Canadian lynx Lynx canadensis (Poole 1995) and bobcat Lynx rufus (Lovallo and Anderson 1996).…”
Section: Discussionmentioning
confidence: 79%
“…Our results did not re¯ect such a preference, as dens were situated in zones of relatively low prey-density. However, female lynx territories in the area under study are small (between 1.86 and 3.22 km 2 ) in comparison with those used by Iberian lynx females in the South of DonÄ ana (Ferreras et al, 1997). So, they do not need to walk a long way to reach the higher prey-density zones inside their territories, whereby any in¯uence of prey distribution on selection would be masked by high availability (Johnson, 1980).…”
Section: What Do Female Lynx Select?mentioning
confidence: 99%
“…Recently classi®ed as the most endangered felid species in the world (Nowel and Jackson, 1996), its total number is around 1000 individuals, distributed among several isolated populations (Rodrõ guez and Delibes, 1992). It is a food and habitat specialist species, highly dependent on the quality and structure of the vegetation for establishing territories and for breeding (Palomares et al, 1991;Ferreras et al, 1997). Lynx females breed once a year, giving birth to one to four cubs which are totally dependent on their mother at least until their third month of life (Aldama, 1993;Ferna ndez and Palomares, own observations).…”
Section: Introductionmentioning
confidence: 99%
“…This observation shows the weakness in measuring range overlap when individual relationships are unknown. Researchers working on other species of lynx have also recorded variable home range overlap within sexes (Breitenmoser et al 1993a;Jedrzejewski et al 1996;Ferreras et al 1997). Generally, male and female home ranges overlap completely while within-sex overlap is usually modest or may be confined to one or two pairs of individuals per study (e.g., .…”
mentioning
confidence: 99%